NKG2D/CD28 chimeric receptor boosts cytotoxicity and durability of CAR-T cells for solid and hematological tumors - Xia Teng; Shance Li; Chaoting Zhang; Huirong Ding; Zhihua Tian; Yuge Zhu; Ting Liu; Guanyu Zhang; Kang Sun; Huimin Xie; Jiaxin Tu; Zheming Lu (Experimental Hematology & Oncology)
Abstract Background CAR-T cell therapy faces challenges in solid tumor treatment and hematologic malignancy relapse, among which the limited persistence of CAR-T cells and target antigen downregulation are prominent factors. Therefore, we engineered an NKG2D/CD28 chimeric co-stimulatory receptor (CCR), leveraging its broad ligand expression on tumors to enhance the antitumor activity of MSLN CAR and CD19 CAR-T cells. Methods We generated MSLN CAR-T and CD19 CAR-T cells co-expressing the NKG2D/CD28 CCR and assessed their antitumor efficacy in vitro and in vivo. CAR-T cell activation, differentiation, and exhaustion were analyzed over time following tumor antigen stimulation. Furthermore, a chronic antigen stimulation model was established using tumor cells with low antigen density to simulate the sustained antigenic pressure encountered in vivo treatment conditions. Results Our study shows that NKG2D/CD28&CAR-T cells exhibit enhanced cytotoxicity against tumor cells, especially those with low antigen density, both in vitro and in vivo. Compared to conventional second-generation MSLN CAR or CD19 CAR-T cells, these dual-targeted NKG2D/CD28&CAR-T cells demonstrate superior sensitivity in recognizing and lysing low-density antigen-expressing lung cancer and leukemia cells, and they are capable of eradicating tumors with low-density antigen expression in vivo. Furthermore, the complementary co-stimulation provided by the 4-1BB and CD28 intracellular domains in the CAR and NKG2D/CD28 promotes cytokine secretion, reduces CAR-T cell exhaustion, and enhances the in vivo persistence of CAR-T cells, significantly improving their antitumor efficacy. Conclusion The combination of CAR and NKG2D/CD28 offers a potent strategy to enhance the cytotoxicity and durability of CAR-T cells. This approach is promising for improving therapeutic outcomes in solid and hematological tumors and preventing recurrence in tumors with low target antigen density.